Melanchra adjuncta Hitched Arches - Pogue, Michael G. (Zenodo, 2010)
17. Melanchra adjuncta (Morrison) Hitched Arches (Fig. 33, Map 18) Identification: Forewing length 15–19 mm. This is a black moth with white markings. The white markings include the basal line, orbicular spot, prominent reniform spot, and a zig-zag subterminal line. There are two small white spots on the costa above both the orbicular and reniform spots and three short dashes along costa between reniform and apex. Hindwing is white, but heavily suffused with black giving a dark gray appearance. The veins are highlighted with black and a faint postmedial line is present in most specimens. There is a series of shallow crescent-shaped lines between the veins along the outer margin. Flight period: May to June and August, apparently double brooded in the Park. Collected localities: North Carolina: Haywood Co., Cataloochee, Purchase Knob, Purchase Knob at house, Purchase Knob NW of house; Swain Co., Big Cove Road site p. (11 specimens) Elevation range: 2040–2600 and 4800–4924 ft. (622–792 and 1463–1501m) General distribution: A common widespread species from Newfoundland across Canada to British Columbia and in the U.S. from Maine south to North Carolina and Arkansas and west to Utah, Idaho, Oregon, and Washington. Larval hosts: This species has a wide range of hosts that include western brackenfern ( Pteridium aquilinum (L.) Kuhn var. latiusculum (Desv.) Underw. ex A. Heller, Dennstaeditiaceae), garden asparagus ( Asparagus officinalis L., Liliaceae), white snakeroot ( Ageratina altissima (L.) King & H. Rob., Asteraceae), Canada goldenrod ( Solidago altissima L., Asteraceae), Virginia strawberry ( Fragaria virginiana Duschesne, Rosaceae), bitter cherry ( Prunus emarginata (Douglas ex Hook.) D. Dietr., Rosaceae), phlox ( Phlox sp., Polemoniaceae), and oldfashioned weigela ( Weigela florida (Bunge) A. DC., Caprifoliaceae) (Tietz 1972). Covell (1984) added clover ( Trifolium spp., Fabaceae), dandelion ( Taraxacum spp., Asteraceae), and elm ( Ulmus sp., Ulmaceae). In Ohio additional host plants include plantain ( ...